Trypanosome Infection in Cattle and Associated Vectors in Etang District of Gambella, Ethiopia - Negesa Tola; Akinaw Wagari; Geremew Haile Lemu; Mohamed Kedir; Haben Fesseha Gebremeskel; Isayas Asefa Kebede (Journal of Parasitology Research)
Background. Bovine trypanosomosis produces significant economic losses due to anemia, loss of body condition, and emaciation. The disease is transmitted biologically by tsetse flies and mechanically by biting flies such as Tabanus and Stomoxys. Therefore, this research is aimed at estimating the prevalence of bovine trypanosomosis and the apparent density of its vectors in the Etang Special District. Methods. A cross-sectional study was employed from November 2016 to April 2017 for the prevalence and entomological survey. Trypanosoma species were identified using buffy coat and Giemsa staining techniques. Besides, the entomological surveys were conducted using NGU, pyramidal, biconical, and monoconical traps. The vectors were identified to their genus level based on their morphological features like size, color, wing venation, and proboscis. Result. A total of 457 bovine blood samples were collected and tested, of these 16 (3.50%) animals were positive for trypanosomosis. Similarly, 13 T. vivax (81.25%) and 3 T. congolense (18.75%) were the trypanosome species detected. The prevalence in the young (2.56%) and adult (3.99%) age groups was not statistically significant (P>0.05). However, there were significant (P<0.05) differences in prevalence between body condition scores, where poor is 6.31%, medium is 1.30%, and good is 0%. Moreover, the difference in mean PCV values between the parasitemic (20.97) and aparasitemic (28.58) groups was statistically significant (P<0.05). Glossina flies were not found, although 1756 Tabanus and 52 Stomoxys biting flies were gathered. Accordingly, the overall apparent density of Glossina flies was zero (0), with biting flies (20.54) recorded per trap per day. Moreover, the apparent density of Tabanus and 52 Stomoxys was 39.01 and 1.18, respectively. Conclusion. This study confirmed that trypanosomosis and abundant mechanical vectors continue to be problems in the study area, resulting in cattle productivity losses. As a result, strategic management and prevention methods for trypanosomosis and associated vectors should be prioritized. Further investigation of vector needs to be conducted to clear out tsetse presence.